Unique Presentation of Intra-Abdominal Testis: Small Bowel Obstruction - Bassiouny, Ibrahim E. (International Scholarly Research Network, 2011)
We describe here a two-year-old male who required urgent laparotomy to relieve a strangulated small bowel caused by internal herniation around an intra-abdominal testis. This clinical presentation has not been reported previously.